The Implementation of Online Learning at The Faculty of Engineering, State University of Makassar in Response To Covid-19 - Syahrul Syahrul; Muliyadi Muliyadi; Shabrina Syntha Dewi (Indonesian Journal of Educational Studies, 2022)
Abstract. This study aims to analyze online learning activities during the Covid-19 pandemic at the Faculty of Engineering, State University of Makassar, including the supporting and inhibiting factors. This study uses a descriptive method with a qualitative approach. The population of this study were students who were attending online lectures during the Covid-19 pandemic at the Faculty of Engineering, UNM, with a sample of 400 students. Data collection was carried out online using a questionnaire via Google Form and interviews. The data were analyzed and interpreted in a descriptive qualitative manner by referring to the formulation of the problem set. The results showed the following; The quality of online learning activities at the Faculty of Engineering UNM during Covid-19 situation was effective. However, some lecturers and students felt the activities were less ideal compared to conventional face-to-face learning; The level of students' understanding of course material was quite good, with varying student learning outcomes. The evaluation of learning outcomes conducted by lecturers is quite varied, including giving independent assignments, structured assignments, formative and summative tests; During the Covid-19 response period at the Faculty of Engineering UNM, institutional support from both the Ministry of Education and the university was quite adequate in the form of providing free internet quotas. The obstacles faced by students and lecturers in online learning include the availability of internet quota, the network is sometimes unstable / bad connection because internet access is not the same in every place. Another obstacle is the schedule of lectures which sometimes collide with one another. Keywords: Evaluation, Implementation, Online Learning, Covid-19